Efficacy of high-dose methylprednisolone and cyclophosphamide in childhood-onset systemic lupus erythematosus - Putu Ayunda Trisnia; Ketut Dewi KUmara Wati; Komang Ayu Witarini; Ida Bagus Ramajaya Sutawan; Hendra Santoso (Indonesian Pediatric Society Publishing House, 2020)
Background Systemic lupus erythematosus (SLE) is a chronic, multisystem, autoimmune disease. Untreated SLE often become progressive and lead to increased risk of mortality. Corticosteroid and cyclophosphamide remain the treatment of choice for severe SLE. Disease activity assessed with SLE Daily Activity Index (SLEDAI). Objective To compare the disease activity of childhood-onset severe SLE at the time of diagnosis, after completion of high dose methylprednisolone, and after three month of cyclophosphamide by using  SLEDAI. Methods This study was conducted in the Division of Pediatric Allergy and Immunology, Department of Child Health, Udayana University/Sanglah Hospital, Denpasar, Bali. Subjects were SLE patient aged 0-18 years who had severe clinical manifestations. Subject received therapy combination of high dose methylprednisolone and cyclophosphamide every 2 weeks for six doses. SLEDAI score was assessed at the time of diagnosis, after completion of high dose methylprednisolone, and after three month of cyclophosphamide. Results During the study period, 51 children were diagnosed as SLE. Twenty-one subjects were included for analysis. Median SLEDAI score at the time of diagnosis was 23 (range 13-39). SLEDAI score after three months of cyclophosphamide was decreased to 2 (range 0-14). Post hoc analysis with Wilcoxon signed-rank test showed the improvement of SLEDAI score at the time of diagnosis and after three months of cyclophosphamide was statistically significant  (Z=-4.016, P<0.0001). Conclusion SLEDAI score reduced after completion of high-dose methylprednisolone and three month of cyclophosphamide therapy.